ASSESSMENT OF RISK FACTORS AND DRUG UTILIZATION PATTERN OF STROKE PATIENTS IN NEUROLOGY DEPARTMENT (World Journal of Current Medical and Pharmaceutical Research, 2020)
Stroke is the second leading cause of death behind heart diseases in 2013 and a major cause of permanent disability. The burden of stroke in terms of mortality, morbidity and disability is increasing across the world. Neuroprotective drugs has become the core treatment, Due to lack of awareness in people of hospitalization very soon after occurrence of symptoms leading to disability. So this study aimed to discuss in detail on risk factors of stroke and drug utilisation patterns to be followed to achieve rational drug use in effective treating and to prevent disability in stroke patients. The risk factors both modifiable and non modifiable risk factors and standard treatment guidelines for effective treatment in both Ischemic stroke and Hemorrhagic stroke were discussed in detail.Objectives:To study the drug prescribing pattern among stroke patients and the indications for which      they have prescribed. To determine the average drug encounter for prescription. To evaluate hazards, then remove or minimise its risk by adding control measures. Materials and Methodology:The current study was a prospective observational study of stroke patients to the department of neurology, Lalitha Super Specialities hospital Pvt Ltd, located in Guntur, Andhra Pradesh. The data collection for the study was conducted between September 2019 to January 2020. Data on demographic parameters, drug prescription pattern and clinical profile was documented.Results:  There was high proportion of  Ischemic strokes reported 81.61% than hemorrhagic stroke 18.39%. There were about 66.14% males affected when compared to 33.85% females. Mostly age group with 61-70 years were mostly affected in both the genders with 33.89% males and 26.49% females. The risk factor hypertension was reported as most prominent one with 80.26% and diabetes mellitus with 52.01% respectively. There was high proportion of Polypharmacy among the study was reported most of the prescriptions contain 8 drugs 21.28%. The most common category of drugs being consumed were antacids 11.30%, vitamins and supplements 11.28%,Nootropics 9.62%, Antihypertensives 9.52%, antiplatelets 9.305 and statins 8.93%.Conclusion:  Prevention is better than cure early identification and management of  risk factors like hypertension, diabetes mellitus and change in life style habits like smoking and alcohol consumption may reduce the risk of stroke. Proper prescribing pattern and monitoring the patients may prevent the ADR’s and drug interactions occurring in stroke patients. Follow up of the patient should be taken for the medication adherence and to prevent relapse. The people with good educational background had the awareness on early identification of stroke symptoms and it’s risk factors.